Effects of active static stretching in power and speed performance - de Oliveira, F. C. L.; Pinto Lopes Rama, L. M. (Brazilian Journal of Biomotricity, 2013)
The objective of this study was to evaluate the influence of the active static stretching on the sport performance in power and speed activities as "countermovement jump" (CMJ) and "20 meters sprint". Twenty two males (24.0±6.2 years old), rugby7 and handball players were randomly separated in two groups (A and B) and submitted to two protocols in two different days separated by 48 hours (1- general warm-up, active static stretching exercises followed by CMJ and sprint test; 2- warm-up and only CMJ and sprint test). The results did not showed any acute effects on the CMJ and sprint performance (p>0.05). There were not significant differences in the average of speed in the sprint between the conditions "with active static stretching" and "without stretching" (22,00 ± 1,13km/h; 21,91 ± 1,20km/h, respectively; p=0.828) and in the average of CMJ (35,71 ± 6,20cm; 36,12 ± 6,08cm, respectively, p=0.788). It is concluded that the active static stretching does not influence the sport performance in power and speed activities in experienced high level athletes.